(untitled) (International Journal of Research in Pharmaceutical Sciences and Technology, 2020)
The aim of the present study was to develop the simple, selective, rapid, precise and economical reverse phase-high performance liquid chromatography (RP-HPLC) method for the simultaneous estimation of levocetirizine and phenylpropanolamine HCl in solid dosage forms. The method was carried out on a Phenomenex Luna C18 (25 cm × 4.6 mm i.d., 5 μ) column with a mobile phase consisting of acetonitrile: 0.5% triethylamine (70:30 v/v, pH 3.0) at a flow rate of 1.2 mL/min. Detection was carried out at 220 nm. The retention time (RT) 1.8 min and 2.6 min for phenylpropanolamine hydrocholride and levocetrizine respectively. The % recovery of standard phenylpropanolamine hydrocholride and levocetrizine was found to be 98.17 to 103.56 and 98.893 to 10.422 respectively. The % recovery of sample phenylpropanolamine hydrocholride and levocetrizine was found to be 101.30 and 100.63 respectively. The validation of the proposed method was also carried out. The proposed method can be used for the estimation of these drugs in combined dosage forms.